Team-based musculoskeletal assessment and healthcare quality indicators: A systematic review. Issue 6 (2nd November 2019) - Chan, Michelle; Le, Christina Y.; Dennett, Elizabeth; Defreitas, Terry; Whittaker, Jackie L.
ABSTRACT: The primary objective of this review was to describe health quality indicator (HQI) outcomes of team-based musculoskeletal (MSK) assessments aimed at directing patient care. Secondary objectives included determining the most commonly assessed HQIs, extent of team collaboration, and the healthcare practitioners that most commonly comprise MSK-assessment teams. This review was registered in the PROSPERO database and conducted according to PRISMA guidelines. Five databases were systematically searched to August 2017. Studies selected met a priori inclusion criteria and investigated an HQI outcome of a primary or intermediate care MSK team-based assessment aimed at directing treatment. Two independent raters assessed study quality [Downs and Black (DB) criteria] and level of evidence (Oxford Centre of Evidence-Based Medicine model). Ten studies were included. The majority were low-quality [median DB score 14/32 (range 6–18)] pre-experimental studies (level 4 evidence). Heterogeneity in methodology and HQIs precluded meta-analyses. Hospital length-of-stay (LOS; 3/10 studies) and pain level (3/10) were the most common HQIs investigated. Teams (9/10) were most commonly comprised of a physiotherapist and another healthcare practitioner. Most teams (8/10) demonstrated low-levels of collaboration. There is limited low-level evidence to suggest that team-based MSK assessments are associated with improved clinical outcomes (i.e., pain, quality-of-life) and shorter LOS.